Non-tariff protectionism – a new setting (Economic and Political Thought, 2015)
The analysis of non-tariff protectionism presented in the article in thecontext of its reasons, forms and influence on international trade results ina conclusion that we deal with a phenomenon that has immanently becomepart of the mechanism of global economy; both in the context of its structuralform and opportunistic manifestations of activeness. Rather paradoxically,the countries that have achieved a high level of economic development try toprotect their financial status with the use of NTM. Non-tariff protectionismdemonstrates its restrictive form especially in the periods of crisis and hitsthe weaker links of international exchange – less developed countries. Thechangeable form of contemporary protectionism measures, often definedas a ‘moving target’, makes liberalization activities more difficult. They aremore and more complex in the light of changes that are taking place inthe contemporary world due to a more and more dynamic scientific andtechnological progress. That is why TBT/SPS have become so important inthe whole range of non-tariff measures and difficulties with curbing theirrestrictive influence occur. Undoubtedly, it is necessary to increase efforts inorder to awaken the conscience about threats resulting from the selfish use ofNTM in international exchange and look for effective ways of fighting againstnon-tariff restrictions. It can be assumed that the efforts on the arena of theWTO and other international organizations that aim at the above-mentionedprinciples will reach an adequate critical mass necessary to start liberalizationactivities in international trade in the predictable future.